The Influence of Islamic Financial Literacy on the Decision to Use Islamic Financial Institutions (Panyabungan III Village Community, Mandailing Natal Regency) - Lubis, Riadoh (AMK : Abdi Masyarakat UIKA, 2024)
This research was conducted in Kel. Panyabungan III District. Mandailing Christmas. The aim of this research is to analyze the influence of sharia financial literacy on the decision to use sharia financial institutions in the Kel.Panyabungan III community. To achieve this goal, research was carried out using community samples from Kel.Panyabungan III, totaling 98 people using the purposive sampling method, while data analysis in this research was validity and reliability testing, classical assumption testing, simple linear regression testing and hypothesis testing, namely t test and R square test (with the help of the SPSS Version 21 program). Based on the research results, sharia financial literacy has a positive and significant effect on the decision to use sharia financial institutions with a value of tcount < ttable or tcount > ttable (13.518 < ttable 1.664 or 13.518 > ttable 1.664). The recommendation that researchers can use is to further improve sharia financial literacy by conducting outreach about sharia financial literacy so that it becomes better in the future.